1992
DOI: 10.1002/cyto.990130514
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Escherichia coli B/r A during agar filtration: Effect on morphometric measurements

Abstract: We have investigated the phenomenon of particle aggregation in a sample of 71,038 Escherichia coli B/r A cells in balanced exponential growth, during preparation for electron microscopy by agar filtration. The bacteria were photographed in a transmission electron microscope and the dimensions and spatial relationships among all the members of each aggregate were recorded using an interactive image processing system. The proportion of aggregated cells, 22%, is much greater than that found by direct count in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Later, electron-microscopic studies confirmed the essential findings and reported only small, apparently random fluctuations in diameter (Harvey & Marr, 1966). Trueba & Woldringh (1980) observed that the average diameter of slow-growing cells decreased gradually as a function of cell length prior to constriction, rising again during the constriction process ; this was later corroborated by Vardi & Grover (1992) elaborate analysis of more than 55 000 cells. Trueba & Woldringh (1980) inferred from their findings that the diameter of individual cells decreases systematically during their elongation, possibly because of the maintenance of a constant surface-to-volume ratio during the cell cycle.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Later, electron-microscopic studies confirmed the essential findings and reported only small, apparently random fluctuations in diameter (Harvey & Marr, 1966). Trueba & Woldringh (1980) observed that the average diameter of slow-growing cells decreased gradually as a function of cell length prior to constriction, rising again during the constriction process ; this was later corroborated by Vardi & Grover (1992) elaborate analysis of more than 55 000 cells. Trueba & Woldringh (1980) inferred from their findings that the diameter of individual cells decreases systematically during their elongation, possibly because of the maintenance of a constant surface-to-volume ratio during the cell cycle.…”
Section: Introductionmentioning
confidence: 77%
“…Schematic representations of the diameter-length correlations r DL and the * Differences between  V and corresponding  L and  D are very highly significant (P 0n001) in all cases, as determined by the test proposed by Miller (Zar, 1999). † Microscopically selected cells : data obtained by Vardi & Grover (1992) diameter-volume correlations r DV as predicted by each of the models are indicated in Fig. 1.…”
Section: Correlations Between Cell Dimensionsmentioning
confidence: 99%
See 3 more Smart Citations